A comparative analysis of the nativity wealth gap - Thomas K. Bauer; Deborah A. Cobb-Clark; Vincent A. Hildebrand; Mathias Sinning (Institute for the Study of Labor (IZA), 2007)
This paper investigates the source of the gap in the relative wealth position of immigrant households residing in Australia, Germany and the United States. Our results indicate that in Germany and the United States wealth differentials are largely the result of disparity in the educational attainment and demographic composition of the native and immigrant populations, while income differentials are relatively unimportant in understanding the nativity wealth gap. In contrast, the relatively small wealth gap between Australian- and foreign-born households exists because immigrants to Australia do not translate their relative educational and demographic advantage into a wealth advantage. On balance, our results point to substantial cross-national disparity in the economic well-being of immigrant and native families, which is largely consistent with domestic labor markets and the selection policies used to shape the nature of the immigration flow.
urn:nbn:de:101:1-2008040222
Keywords: 330; Vermögensverteilung; Migranten; Bildungsniveau; Lohnstruktur; Australien; Deutschland; USA